Quick guide to survive the 'gender ideology' - Cassal, Luan Carpes Barros; Pereira, Vanessa Marinho (Revista Hipótese, 2016)
The so-called 'Gender Ideology' causes panic in Brazil - children and adolescents are at risk of theories and practices of postmodern deconstruction. But do not worry yourself, teacher. Your problems are over. Follow the instructions in this short manual, produced from legislation analysis and philosophical inspirations to make your work easier.
Keywords: School; Childhood; Sexuality; Gender